Reinventing diversity : transforming organizational community to strengthen people, purpose, and performance - Ross, Howard J. (Lanham, MD : Rowman & Littlefield, 2013)
"In Reinventing Diversity, one of America's leading diversity experts explains why most diversity programs fail and how we can make them work. In this inspiring guide, Howard Ross, uses interviews, personal stories, statistics, and case studies to show that there is no quick fix, no easy answer. Acceptance needs to become part of the culture of a company, not just a mandated attitude"--Publisher.
Why does it matter? -- Why most diversity programs haven't succeeded -- The background is background -- The conundrum of community -- Uncovering the background of diversity -- Paradigm shift 1: Transforming cultural competency into competitive advantage -- Paradigm shift 2: how can we know bias when we can't even see it in ourselves? -- Memes, myself and I : understanding perceptual identity -- Developing diversity mastery : understanding your wiring -- "It's the system, stupid!": Paradigm shift 3: moving from events to culture-based systems change -- The eight basic principles of organizational community -- Creating cultures that work -- Walls come tumbling down -- A new way home.
"Published in association with the Society for Human Resource Management."
"Foreword by Julianne Malveaux"--Cover.
Includes bibliographical references (pages 273-280) and index.
Keywords: Diversity in the workplace; Cultural pluralism